GANTI KERUGIAN TANAH MILIK IVANNA SULISTIO THIO SESUAI TAHAP PELAKSANAAN PENGADAAN TANAH - Muhammad Arsy Revaldy; Nevia cahyana, Intan; Arsy Revaldy, Muhammad (Faculty of Law, Universitas Trisakti, 2023)
Ivanna Sulistio Thio has filed a protest regarding the incompatibility of compensation for the administration of land acquisition in the province of East Kalimantan. The area of land that has been given compensation is only 842 m2, whereas the area of land used for land acquisition is 5428 m2. The problem posed in this study is whether Ivanna Sulistio Thio should receive compensation for her land tenure in accordance with the Land Acquisition Implementation Stage based on Law Number 2 of 2012 and whether the Samarinda District Court's decision, Number 28/Pdt.G/2018/PN Smr, is in accordance with that law regarding land acquisition for development in the public Interest. The research method uses descriptive research that is normative, research data collection uses library research, data is analyzed using qualitative methods, drawing conclusions using deductive logic. The results of the research and discussion are that the value of compensation given by the executor of land acquisition is not in accordance with the principle of justice. The conclusion of the research is that the compensation given by the executor is not in accordance with the principles of land acquisition.